Analisa Hasil Pengelasan Mahasiswa Program Studi Alat Berat Poliban dalam Pembelajaran Basic Welding Technic Sebagai Kontrol Kualitas - Ahmad Hendrawan; Noor Rahman; Muhammad Hasbi (Politeknik Negeri Samarinda, 2022)
One of the Study Programs in the Poliban Mechanical Engineering Department is the Heavy Equipment Study Program. One of the courses contained in the Heavy Equipment Study Program Curriculum is Basic Welding which is taken in semester IV with a weight of 2 credits. To find out whether students really master their field, a reliable evaluation tool is needed, because this evaluation tool must really be able to reveal whether the results of student practice have met the criteria or not. The purpose of this study was to determine the quality of the welds on the practical results of semester IV students of the Mechanical Engineering Department, Heavy Equipment Study Program, using tensile and macro testing. It is hoped that the target of student lectures can be achieved. This research took the population of the Poliban Heavy Equipment Study Program Semester IV. While the research sample was taken 18 students who carry out welding practice. Based on the yield stress obtained, there are 2 specimens or the equivalent of 11.11%, which is below the standard of the Yield Strength of ST-37 steel or the equivalent of AISI 1045, which is ≥ 310 N/mm2, so the percentage of acceptable student welding results is 88. 88%. Based on the results of the visual inspection, there were four specimens that broke off in the weld area or equivalent to 22.22% of the test results, so that the percentage of acceptable student welding results based on the visual inspection results was 77.78%.